Imago Dei Distortion as An Analytical Framework for Adolescent Identity Crisis in The Digital Age - Tirza Froulen Bella; Diniyarti Rara Bolu (Sekolah Tinggi Teologi Transformasi Indonesia, 2026)
The development of social media has transformed the way adolescents construct and understand their self-identity. Previous studies have predominantly examined adolescent digital identity from psychological and sociological perspectives, particularly in relation to social validation, anxiety, and mental well-being, but have not yet been able to explain adolescent digital identity crises as an anthropological-theological issue related to the Imago Dei. This study aims to analyze the dynamics of adolescent digital identity from the perspective of the theology of the Imago Dei, identify the forms of identity distortion that emerge, and formulate their implications for Christian Religious Education. This research employs a qualitative library research approach using critical thematic analysis and conceptual analysis within an interdisciplinary framework integrating theology, developmental psychology, and digital media studies. The findings reveal that adolescent digital identity is shaped by algorithmic logic, a culture of visibility, and mechanisms of social validation that encourage the formation of performative and fragmented identities. From the perspective of the Imago Dei, these conditions reflect identity distortion characterized by ontological reduction, identity dislocation, and a shift in relationality from intrinsic to instrumental. These findings indicate that the identity crisis experienced by adolescents in the digital era is not merely psychosocial but also theological in nature. This study proposes the concept of “Distortion of Imago Dei” as a new interdisciplinary-theological framework for understanding adolescent identity crises in the digital era, while also serving as a foundation for reconstructing contextual Christian Religious Education